FREE CASH FLOW, OUTSIDER OWNERSHIP, LEVERAGE, DAN KEBIJAKAN DIVIDEN TERHADAP KOS KEAGENAN - Gerianta Wirawan Yasa; Ni Luh Ayu Sukrisna Dewi (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2016)
The purpose of this study was to determine empirical evidence influence of free cash flow, leverage, institutional ownership, foreign ownership and dividend policy on agency cost. Agency relationships inflict agency conflicts that trigger agency cost. This research was conducted on all companies listed in Indonesia Stock Exchange in the year of observation 2012-2014 Samples were selected by purposive sampling and acquired 38 companies. The analysis technique used is multiple linear regressions and there is additional sensitivity test to strengthentheresearch results, this research use different proxy agency cost such as selling and general administrative and asset turnover.Research results show that the free cash flow and institutional ownership has a positive influence on the agency cost, leverage negatively affect the agency cost, and foreign ownership and dividend policy does not affect the agency cost. While in sensitivity test is known that selling and general administrative proxies better able to explain agency cost compared with asset turnover.